Typological and cumulative approaches to risk and adversity in Child and Adolescent Mental Health Services (CAMHS): Retrospective cohort analysis in South London - Barry Coughlan; Nicole Marshall; Matt Woolgar; Julia Mannes; Paige Erkiert; Ayla Humphrey; Jack Smith; Taliah Drayak; Francesca Crozier-Roche; Tessa Morgan; Dustin Hutchinson; David Graham; et al. (Comprehensive Psychiatry)
Background: Childhood adversity is robustly associated with mental ill-health. Yet questions remain about how different ways of conceptualising adversity relate to psychiatric diagnoses and service activity. This research aims to examine associations between typological and cumulative conceptualisations of adversity, and psychiatric diagnosis and service activity. Methods: We analysed risk assessment data from 21,072 young people attending mental health services in South London. These assessments include items relating to maltreatment, parental mental health difficulties, substance misuse, self-harm, and violent behaviour. Using latent class analysis, we identified the following risk typologies: ‘Maltreatment and externalising behaviours’ (n = 971, 4·6 %), ‘Maltreatment but low risk to self and others’ (n = 2526, 12·0 %), ‘Anti-social behaviour’ (n = 2669, 12·7 %), ‘Inadequate caregiver supervision and risk to self and others’ (n = 907, 4·3 %), ‘Risk to self but not to others’ (n = 1725, 8·2 %), and ‘Mental health needs but low risk to self and others’ (n = 12,274, 58·2 %).Two cumulative risk models were created: 1) all risk items 2) Adverse Childhood Experiences-related cumulative risk (ACES-CR). Controlling for gender, ethnicity, age, and deprivation, we examined associations between risk typologies, cumulative risk, and the following outcomes: 1) psychiatric diagnosis 2) face-to-face appointments 3) missed appointments 4) referral to social services. Outcomes: Risk in its various conceptualisations was consistently and robustly associated with conduct disorder. Risk also tended to be associated with more face-to-face appointments, missed appointments, and referral to social services. Associations between individual risk typologies and psychiatric diagnosis and service activity are discussed. Interpretation: Our findings suggest that typological and cumulative approaches to risk and adversity can produce unique insights about diagnostic practices and service activity. This work provides further evidence for the contribution of contextual factors to mental ill-health and further work is required to explore the longer-term trajectories of these young people.